PERAN GURU DALAM MENINGKATKAN MANAJEMEN MUTU PENDIDIKAN DI INDONESIA - Afriantoni; Azizah, Dina Nur; Ayu, Wulan Rahma (Information Technology Education Department, 2025)
Teachers have an important role in learning management. Since teachers carry out the teaching and learning process, their teaching effectiveness has a significant impact on the overall success of education. The findings of theoretical studies suggest that if teachers can fulfill their role as learning managers by using teaching and learning facilities to create learning situations, learning management in their functional duties will be carried out effectively and efficiently. The roles and responsibilities of teachers are very important in the field of education. “With all the changes in the quality of national education, it is difficult to isolate many of the issues related to the presence of instructors as they are the most important component of the teaching and learning process, both in formal and informal learning pathways. Learning is essentially a causal process, with the teacher as the main cause of student learning. Therefore, teachers must be able to determine the right learning strategy to encourage students to participate in learning activities actively, productively and effectively. Teachers must pay attention to their students' readiness, maturity, and behavior when teaching. Therefore, teachers have an important role and strategy to create a good and enjoyable learning environment and help students achieve goals as well as possible.